The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1093/oxfordjournals.humrep.a138327
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of interleukin-1β correlates with prostaglandin E2 and F2α in human pre-ovulatory follicular fluid

Abstract: To investigate the role(s) of interleukin-1 beta (IL-1 beta) in human ovarian function, we measured the concentrations of IL-1 beta, prostaglandins (PGs) and steroids in follicular fluid of 90 stimulated ovaries, with reference to oocyte maturation. Concentrations of IL-1 beta were significantly higher in the follicles from which mature oocytes were recovered than in follicles from which oocytes could not be recovered (P < 0.05). IL-1 beta concentrations also increased in association with oocyte maturation. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This effect may be triggered by sphingomyelin hydrolysis and ceramide production (Santana et al 1996). Finally, in vivo IL-1 concentration in human follicular fluid is correlated with PGE2 and PGF2 concentrations (Watanabe et al 1994). By using an ovarian perfusion model, Peterson et al (1993) confirmed these observations in the rat.…”
Section: Production and Activation Of Proteolytic Enzymesmentioning
confidence: 54%
See 1 more Smart Citation
“…This effect may be triggered by sphingomyelin hydrolysis and ceramide production (Santana et al 1996). Finally, in vivo IL-1 concentration in human follicular fluid is correlated with PGE2 and PGF2 concentrations (Watanabe et al 1994). By using an ovarian perfusion model, Peterson et al (1993) confirmed these observations in the rat.…”
Section: Production and Activation Of Proteolytic Enzymesmentioning
confidence: 54%
“…Their results lead us to conclude that IL-1 intervenes in PG production, mainly by acting on cyclooxygenase-2 (COX-2) synthesis. Actually, IL-1 induces in vitro PGE2 and PGF2 production by granulosa cells (humans: Watanabe et al 1993;rats: Hurwitz et al 1995;cattle: Acosta et al 1998). Moreover, it has been demonstrated in vitro that IL-1 induces an increase in 6 keto-PGF1 , PGE2 and PGF2 in cultured rat preovulatory follicles (Brännström et al 1993b) and bovine granulosa cells (Nothnick & Pate 1990).…”
Section: Production and Activation Of Proteolytic Enzymesmentioning
confidence: 99%
“…In particular, macrophages have been recognised for their role in inducing progesterone production in granulosa cells in coculture experiments in mice (Kirsch et al 1981), humans (Halme et al 1985) and pigs (Standaert et al 1990) without concomitant granulosa cell proliferation. Two potent cytokines secreted by macrophages, interleukin-1 and tumour necrosis factor-a, have been shown to stimulate both progesterone and prostaglandin synthesis (Nakamura et al 1990, Kokia et al 1992, Watanabe et al 1993, Brannstrom et al 1994, Roby et al 1999 and these may interact with other macrophage-derived factors to fine-tune gonadotrophin regulation of corpus luteum function and demise (Wuttke et al 1997). In vitro experiments from human granulosa cells further implicate cytokines originating from ovarian cells in promoting proliferation and/or functional activation of steroidogenic cells (Jasper et al 1996).…”
Section: S O'leary and Othersmentioning
confidence: 99%
“…Furthermore, their production seems to be regulated by some cytokines, i.e., interleukin (IL)-I and tumor necrosis factor-tx (TNF-e0, because they can stimulate monocytes to produce PGs (6,7).…”
Section: Introductionmentioning
confidence: 99%